Representation of Family Communication in the Film “Bila Esok Ibu Tiada” Through Fiske’s Lens - Idiani, Intan; Ammelia, Euis; Intan, Dian Mustika (Program Pascasarjana UIN Sumatera Utara, 2025)
This study analyzes the representation of family communication in the film